Polynuclear Complexes of Ni(II) and Zn(II) with Lanthanide(III) Schiff N-Isonicotinamidosalicylaldimine - R. Rao, Thatavarthi; Singh, Genda; A. Khan, Israr; S.S.J. Sastry, Pariti (Asian Journal of Chemistry, 2010)
Polynuclear complexes of Ni(II) and Zn(II) chlorides with potassium bis(N-isonicotinamidosalicylideniminato) lanthanate(III) have been prepared and characterised by elemental analyses, magnetic susceptibility, infrared and electronic spectral measurements. Reliable information relating to metal-ligand bonding and geometries of the complexes have been inferred from the infrared and electronic spectral data.